2010
DOI: 10.1590/s1519-69842010000500022
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial potential of some plant extracts against Candida species

Abstract: The increase in the resistance to antimicrobial drugs in use has attracted the attention of the scientific community, and medicinal plants have been extensively studied as alternative agents for the prevention of infections. The Candida genus yeast can become an opportunistic pathogen causing disease in immunosuppressive hosts. The purpose of this study was to evaluate dichloromethane and methanol extracts from Mentha piperita, Rosmarinus officinalis, Arrabidaea chica, Tabebuia avellanedae, Punica granatum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 25 publications
3
74
0
7
Order By: Relevance
“…Other studies in the literature have reported on the antifungal effects of S. cumini on C. albicans (Oliveira et al 2007;H€ ofling et al 2010;Santos et al 2012), but have not further described its mode of action and effects on biofilm morphology and viability (see further in the discussion). As to the chemical profile, the major compounds found in the extract of the leaves in this study were saponins.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in the literature have reported on the antifungal effects of S. cumini on C. albicans (Oliveira et al 2007;H€ ofling et al 2010;Santos et al 2012), but have not further described its mode of action and effects on biofilm morphology and viability (see further in the discussion). As to the chemical profile, the major compounds found in the extract of the leaves in this study were saponins.…”
Section: Discussionmentioning
confidence: 99%
“…B. Verl (Bignoniaceae) leaf extract has been used as an infusion to treat diseases such as gastric ulcers, intestinal colic, diarrhea, inflammation, infections, and anemia (Siraichi et al, 2013). The antioxidant (Siraichi et al, 2013), liver protective (Lima de Medeiros et al, 2011), and antimicrobial activity (Hofling et al, 2010) of this plant has been reported recently. Antimicrobial activity of hydroethanol extract of A. chica leaves was tested by the broth microdilution method using a panel of bacteria and yeast of clinical interest.…”
Section: Arrabidaea Chicamentioning
confidence: 99%
“…Many studies are being carried out to find plant species with potential antifungal activity Höfling et al, 2010), because synthetic drugs may exhibit high toxicity to patients (Araújo et al, 2004). Substances more efficient against pathogenic microorganisms and less toxic to the patient could be isolated from vegetal species (Ostrosky, 2009).…”
Section: Introductionmentioning
confidence: 99%